Effects of auditory white noise stimulation on sustained attention and response time variability - Egeland, Jens; Lund, Olaf; Kowalik-Gran, Iwona; Aarlien, Anne Kristine; Söderlund, Göran B. W. (Frontiers in Psychology, 2023)
The moderate brain arousal model" claims that white noise improves attention by optimizing brain arousal. We analyze Conners' Continuous Performance Test-3 (CCPT-3) performance, expecting to find reduced reaction time variability with noise mediated by decrease under long event-rates and in later parts of the test, indicating that noise reverse fall in phasic and tonic arousal.Sixty-five children with high or lower ADHD-symptoms from a child psychiatric unit, succeeded to complete the CCPT-3 with and without white noise.Noise reduced overall variability, improved performance in later parts of the test, and reduced response variability under the longest event rate particularly in the high symptoms group. No overall change in omissions and commissions, but the high symptoms group made fewer omissions during noise compared the low symptom group.The study indicates an arousal effect of noise but should be replicated with other noise variants and amplitudes to improve effect and compliance.